Clinical features and histological types of 35 cases of carcinoma esophagus: experience from two hospitals in Bangladesh (IMC Journal of Medical Science, 2017)
Background and objectives: Esophageal malignancy is a fatal disease. Squamous cell cancer and adenocarcinoma are two most common types. The present study aimed to describe demographic characteristics, clinical features, histological types and associated among the selected Bangladeshi patients with esophageal cancers.Methods: This cross-sectional descriptive study was conducted from January to December 2016 at two hospitals in Bangladesh. Total 35 adult patients diagnosed as having esophageal cancer were consecutively and purposively included in this study. Age, gender, history of chewing betel nut and smoking, clinical presentation and laboratory parameters were recorded systematically in a predesigned data sheet.Results: Among the 35 patients with esophageal cancer, 80% were more than 50 yrs of age while 71.4% and 28.6% were male and female respectively. Out of these cases, 27 (77.1%) had squamous cell carcinoma (SCC) and 8 (22.9%) had adenocarcinoma. Out of 27 SCC, 15 (55.6%) had lesion in mid-esophagus, 9 (33.3%) in lower and 3 (11.1%) in upper esophagus. All adenocarcinoma were present in lower esophagus. History of smoking and chewing betel nut were not significantly associated with esophageal cancers.Conclusions: Esophageal carcinoma was common in elderly male and SCC was more frequent compared to adenocarcinoma. Further study with larger number of samples is required to determine the role of smoking and betel nut chewing in esophageal cancers in Bangladeshi population.IMC J Med Sci 2017; 11(2): 36-39